2006
DOI: 10.1021/jm0509795
|View full text |Cite
|
Sign up to set email alerts
|

A Selective Estrogen Receptor Modulator for the Treatment of Hot Flushes

Abstract: A selective estrogen receptor modulator (SERM) for the potential treatment of hot flushes is described. (R)-(+)-7,9-difluoro-5-[4-(2-piperidin-1-ylethoxy)phenyl]-5H-6-oxachrysen-2-ol, LSN2120310, potently binds ERalpha and ERbeta and is an antagonist in MCF-7 breast adenocarcinoma and Ishikawa uterine cancer cell lines. The compound is a potent estrogen antagonist in the rat uterus. In ovariectomized rats, the compound lowers cholesterol, maintains bone mineral density, and is efficacious in a morphine depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…The third-generation of SERMs include the compounds discovered after raloxifene that display further improvements in tissue specificity. An example is LSN2120310, (R)-(+)-7,9-difluoro-5-[4-(2-piperidin-1-ylethoxy)phenyl]-5H-6-oxachrysen-2-ol, which is based on the raloxifene chemical scaffold; it displays agonist activity in the bone and antagonist activity in the breast and uterus, but unlike tamoxifen and raloxifene it may actually prevent hot flashes (Wallace et al, 2006). Going forward, 724 the next generation of SERMs will build upon our understanding of ligand-specific regulation of individual genes within a single tissue, not only displaying tissuespecific agonist or antagonist activity but also differential upregulation or downregulation of specific genes within a single cell type (Bramlett and Burris, 2003).…”
Section: Nuclear Receptors and Their Selective Modulatorsmentioning
confidence: 99%
“…The third-generation of SERMs include the compounds discovered after raloxifene that display further improvements in tissue specificity. An example is LSN2120310, (R)-(+)-7,9-difluoro-5-[4-(2-piperidin-1-ylethoxy)phenyl]-5H-6-oxachrysen-2-ol, which is based on the raloxifene chemical scaffold; it displays agonist activity in the bone and antagonist activity in the breast and uterus, but unlike tamoxifen and raloxifene it may actually prevent hot flashes (Wallace et al, 2006). Going forward, 724 the next generation of SERMs will build upon our understanding of ligand-specific regulation of individual genes within a single tissue, not only displaying tissuespecific agonist or antagonist activity but also differential upregulation or downregulation of specific genes within a single cell type (Bramlett and Burris, 2003).…”
Section: Nuclear Receptors and Their Selective Modulatorsmentioning
confidence: 99%
“…A common adverse event associated with SERMs to date seems to be an increased incidence of hot flushes and warrants further study to determine a solution. There are several novel agents being evaluated to address hot flashes [207][208][209][210]. Bazedoxifene has been shown to maintain or increase BMD, reduce bone turnover, and decrease the risk of new vertebral fracture in postmenopausal women without evidence of endometrial or breast stimulation in large, prospective phase III studies [196][197][198].…”
Section: Discussionmentioning
confidence: 99%
“…We will now 133 briefly consider the evolving subcellular mechanism of estrogen action in its target Early studies with clomiphene used a mixture of geometric isomers [53,57,207 58]. The cis and trans isomers were separated [67] and each has been reported to Structure-Activity Relationships in the Rat 7 208 possess different biologic activities [68][69][70]; however, some controversy 209 surrounded the designation of the isomers in relation to their observed biologic 210 properties. They were originally labeled as geometric isomers!…”
mentioning
confidence: 99%
“…The estrogenonly arm of this study indicated increased risks for coronary disease and thromboembolism (Anderson et al, 2004). The search for selective estrogen receptor modulators with favorable effects on menopausal symptoms and bone health, but without increasing breast cancer and cardiovascular risk, is an area of intense pharmaceutical activity (Riggs and Hartmann, 2003;Wallace et al, 2006). Nevertheless these adverse reports have led to unprecedented numbers of women abruptly stopping ERT medications containing synthetic sex steroids (Mclntosh and Blalock, 2005).…”
Section: Introductionmentioning
confidence: 92%